VIRTUE THEORY AND THE MORAL CHALLENGE IN THE NIGERIAN EDUCATIONAL SYSTEM (2017)
Virtue theory holds that the cultivation of good character is an essential moral goal and the focus of moral education is to raise rational and morally virtuous persons. This is rooted in a philosophical account of the moral life and conduct from which educational aims are derived. Previous studies on challenges in the Nigerian educational system focussed on religious instruction to the neglect of moral education. This study, therefore, examined virtue theory which emphasises the promotion of good character and conduct, with a view to establishing its importance in grooming morally virtuous persons and curbing moral decadence in the Nigerian educational system. The study adopted Aristotle’s theory of Habituation, which emphasises reason, habit and training as features that collectively determine the emergence of a moral person. Eleven relevant texts in Ethics: Aristotle’s Nicomachean Ethics (NE), Eudemian Ethics (EE), MacIntyre’s After Virtue (AV), Nel Nodding’s Care Ethics (CE) and Habermas’s Discourse Ethics (DE), and twenty-five in Philosophy of Education including Carr’s and Steutel’s Virtue Ethics and Moral Education (VEME), Akinpelu’s Essays in Philosophy and Education (EPE), Halstead’s and Mclaughlin’s Education in Morality (EM), Gilligan’s In a Different Voice (IDV) and Sprod’s Philosophical Discussion in Moral Education (PDME), were purposively selected because they dwelt on virtue theory, habit training, practical reason and educational development. Conceptual analysis was employed to clarify concepts such as education, morality and religion, while reconstruction was used to show the centrality of virtue theory to resolving moral challenges in the Nigerian educational system. Texts in Ethics emphasised that the cultivation of moral virtue requires practical wisdom, emotions, choices, values, perceptions, attitudes, expectations and sensibilities, the possession of which result in morally virtuous individuals (NE, EE, DE). Religious education focussed on personal faith, beliefs, attitudes and practices of a particular religion and therefore, is inadequate in inculcating virtues that would transcend religion and other divides to promote positive attitudinal change in persons (EPE, IDV). In Philosophy of Education the upbringing of the child requires the concurrent development of both the moral and intellectual components of education as embedded in the cultural and social practices of a people (VEME, EPE, AV). Critical intervention revealed that religious approach to the problem of moral decadence is inadequate and that an effective framework for resolving the moral challenge in Nigerian educational system requires habituation and the training of persons in some positive cultural and social values, which a training in religious education alone cannot provide. Moral challenge in the Nigerian educational system has persisted due to emphasis on religious instruction, which focussed on beliefs and practices of a particular religion to the neglect of moral education. Therefore, virtue theory, will resolve the moral challenge in the Nigerian educational system.